PRODUCTION EFFICIENCY ANALYSIS OF RICE WITH JAJAR LEGOWO METHOD ON SRI IN LIMA PULUH KOTA REGENCY - Zia Aznur, Tifany; R. Pulungan, Delyana; Febriamansyah, Rudi; Ifdal, Ifdal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aimed to analyzed the factors that affect the rice production, and to determine the level of production efficiency of rice with jajar legowo method on SRI in Nagari Situjuah Gadang. The study was conducted with survey method on 30 samples taken by proporsionate purposive sampling. The data analysis used multiple linear regression analysis and production efficiency analysis of Cobb-Douglass. The results showed that the use of factors of production of seeds, organic fertilizer, inorganic fertilizer and labor impact together on rice production with a calculated F value of 52.387. Partially, the use of each factor of production have a significant effect on rice production. The results of production efficiency analysis showed that the production process is already technically efficient with a value TER 0,97. The use of factors of production of seed, fertilizer organic and inorganic fertilizer are not economically efficient, and the use of production factor of labor is economically inefficient. Scale rice farming is at a level increasing returns to scale so that the level of optimum use of production factors can not be determined. To increase production, farmers should use as much as 1-3 seeds per planting hole; pay attention to the rules of the use of balanced fertilizer; increase the amount of organic fertilizer use; and reduce the use of labor at harvest.